Indicators of hydro-ecological alteration for the rivers of the United States. (January 2021) - George, Robert; McManamay, Ryan; Perry, Denielle; Sabo, John; Ruddell, Benjamin L.
Graphical abstract: Highlights: Understanding fish-flow relationships is vital for water management decision-making. Fish-flow relationships & impact thresholds are present across the U.S. Native fish-flow relationships are variable across the U.S. Western basins have insufficient field data to establish relationships and thresholds. Abstract: Recent decades have produced a river of field data linking hydrologic alteration to fish populations in hundreds of U.S. river systems. Adverse impact thresholds and relationships between flow alteration and fish populations are key for advancing environmental flow conservation and environmental flow regulations in U.S. waterways. Prior work has established relationships in individual rivers and fine scale basins, but not for large basins or at national scale. As a first step toward establishing consistent fish-flow relationships and adverse impact thresholds in every US waterway, we analyze a nation-wide aggregated dataset from McManamay et al., 2017 containing co-located estimates of altered hydrologic metrics (HMs) for flow and native fish richness. In each medium sized river system (HUC4) we (1) identify the hydrologic metrics that most powerfully explain observed impacts on native fish richness, (2) estimate an adverse resource impact threshold defining excessive flow alteration, and (3) attribute the main causes of observed flow alteration. Strong empirical relationships between hydrologic metrics and native fish richness are thus established for most HUC4 basins in the continental U.S., and can be used as guidelines for science-based management. However, the findings underline a major aquatic ecology data gap in the western U.S. where a lack of statistically adequate field observations currently prevent clear results, and this gap will hinder science-based management of those river basins until it is filled.